Digital map update using carrier phase handheld GPS - Mat Amin, Zulkarnaini (Fakulti Ukur dan Harta Tanah, 1996)
The vast infrastructure development requires a quick and cost-effective tool to update or providing of fresh data to digital data base. The conventional method of positioning is very slow and time-consuming. Certainly a nevv technology such as the Global Positioning System (GPS) will help map makers to perform such mapping task. The main aim of this paper is to utilize the advent of low-cost, carrier phase handheld GPS in map updating using differential techniques. The method investigated used hybrid receivers, processing through the RINEX format. The seamless GPS data are then overlaid using AutoCad software to produce the final output. The significant consequence of the output is that GPS techniques using integrated receivers seems to be cost-effective and adequate for digital mapping and an effective method of data acquisition.